2015
DOI: 10.1084/jem.20131675
|View full text |Cite
|
Sign up to set email alerts
|

Modular expression analysis reveals functional conservation between human Langerhans cells and mouse cross-priming dendritic cells

Abstract: In depth phenotyping and functional analysis of skin dendritic cell subsets suggests that the function of Langerhans cells may not be conserved between mouse and human and supports the idea that human Langernhans cells may be a relevant therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 57 publications
(97 reference statements)
7
72
2
Order By: Relevance
“…Thus, it is also possible that CD5 expression on DCs serves as a pattern recognition receptor and mediates the production of proinflammatory cytokines upon activation. This is intriguing, as none of the other known receptors for zymosan (i.e., TLR-2 or dectin-1) are present on CD5 + LCs and dermal CD1a dim CD5 + DCs; however, they are highly abundant on the dermal CD14 + DCs (25). Whether CD5 recognizes other pathogen-associated molecular patterns besides zymosan remains to be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is also possible that CD5 expression on DCs serves as a pattern recognition receptor and mediates the production of proinflammatory cytokines upon activation. This is intriguing, as none of the other known receptors for zymosan (i.e., TLR-2 or dectin-1) are present on CD5 + LCs and dermal CD1a dim CD5 + DCs; however, they are highly abundant on the dermal CD14 + DCs (25). Whether CD5 recognizes other pathogen-associated molecular patterns besides zymosan remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is not known whether the function of mouse and human CD5 + DCs is similar. A recent study by Artyomov and Munk et al (25) showed that human and mouse DCs that are similar anatomically and, in fact, may have different functions. This may add to the complexity of studying a disease such as psoriasis, which is only transient in current rodent models but chronically affects millions of humans.…”
Section: Cd1cmentioning
confidence: 99%
“…Some differences between human and murine Langerhans cells (LCs) have been suggested (76, 77). One difference may be due to their ability for cross-presentation (76).…”
Section: Heterogeneity Of Mature Dendritic Cellsmentioning
confidence: 99%
“…Therefore, there is a possibility that degraded HIV peptide through langerin or other molecules is cross-presented to MHC I, even in HIV non-infected mLCs and epidermal LCs. Interestingly, murine LCs cannot cross-present extracellular antigens, whereas human LCs can cross-present [58]. This means that human LCs were highly adept at inducing primary CTL responses.…”
Section: Discussionmentioning
confidence: 99%